The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/jsbed-07-2017-0221
|View full text |Cite
|
Sign up to set email alerts
|

Internationalisation commitment of emerging market firms

Abstract: Purpose Enhancing firm commitment towards internationalisation is an important step towards ensuring successful international performance. However, there is limited research on this topic for emerging market firms. The purpose of this paper is to investigate the factors that influence the internationalisation commitment of emerging market firms located in two Latin American countries with different institutional environments. Design/methodology/approach This study proposes and tests a conceptual model that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 110 publications
(148 reference statements)
0
16
1
2
Order By: Relevance
“…A reluctance to participate in surveys still persists in Chile, making empirical studies difficult, despite efforts to increase the response rate. This situation is not unique and the literature (Bianchi et al, 2018) indicates that the general response rate of companies is decreasing worldwide. Table 1 illustrates the sample characterisation by economic activity.…”
Section: Sample and Data Sourcesmentioning
confidence: 99%
“…A reluctance to participate in surveys still persists in Chile, making empirical studies difficult, despite efforts to increase the response rate. This situation is not unique and the literature (Bianchi et al, 2018) indicates that the general response rate of companies is decreasing worldwide. Table 1 illustrates the sample characterisation by economic activity.…”
Section: Sample and Data Sourcesmentioning
confidence: 99%
“…A recent study in France showed that 84 per cent of SMEs want to increase their export activity – an increase of five percentage points on 2016 (Euler Hermes, 2018). Research has shown that firm commitment towards internationalisation is an important first step towards achieving successful international performance (Bianchi et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Anwar, Shah, & Khan, 2018), Other reasons cited for the trend include a high degree of local competition (Neubert & Van Der Krogt, 2020), lack of state support (Wu & Deng, 2020), poor technology (Li & Ding, 2017), and unstable market conditions (Adomako, Amankwah‐Amoah, Dankwah, Danso, & Donbesuur, 2019). At the same time, the potential benefits of internationalization (e.g., high profitability, sales growth, stable markets, and opportunities), motivate emerging small and medium‐sized enterprises (SMEs) to enter into foreign markets (Bianchi, Carneiro, & Wickramasekera, 2018; Zhang, Ma, Wang, & Wang, 2014). However, all the SMEs cannot make a successful international entry due to several weaknesses and constraints: lack of support, deficiency of resources, regulations, and poor managerial skills (Anwar et al, 2018; Hutchinson, Fleck, & Lloyd‐Reason, 2009; Lin & Chaney, 2007; Lu & Beamish, 2001).…”
Section: Introductionmentioning
confidence: 99%